1877 : America's year of living violently - Bellesiles, Michael A. (New Press : Distributed by Perseus Distribution, 2010)
Describes a time of upheaval in America--when the country was in a deep economic depression, white supremacists roamed the South, and a nationwide railroad strike led to bloodshed--and discusses how the events of 1877 also fueled cultural and intellectual innovation.